Group Psychotherapy for Chronic Pain: A Protocol (Brazilian Journal of Behavioral and Cognitive Therapy, 2014)
This article is about psychotherapy for chronic pain. A protocol for group treatment is provided, as a result of efforts to integrate clinical practices that address several psychological and psychosocial mechanisms that maintain chronic pain. Contemporary behavioral strategies are assimilated, together with skills training and psycho-education. The group format makes it easier to target a range of problems while they occur in vivo during the sessions. The protocol integrates different strategies that target social, interpersonal, and experiential changes into a portable set that can be applied to a variety of medical and community settings. This can improve access to effective multidimensional treatment for people with chronic pain. The protocol is intended for professionals in the field, but also lends itself to efficacy research in psychological intervention for chronic pain.
Keywords: chronic pain; behavior therapy; treatment protocol